Regional Anesthesia In Patients With Parkinson's Disease - Ardi Pramono; Yossy Budi Setiawan; Akhmad Syaiful Fatah Husain; Silvia Rakhmadani (Al-Makki Publisher, 2022)
Parkinson's disease is a degenerative disease of the central nervous system, which occurs in 1% of the population over 60 years of age. This disease is caused by the loss of dopaminergic nerve fibers in the basal ganglia of the brain due to an immune response. Parkinsonism is the name given to a clinical syndrome consisting of disorders of voluntary movement (hypokinesia), stiffness, and tremors. The typical pathological picture is the destruction of nerve cells containing dopamine in the substantia nigra of the basal ganglia. The selection of anesthetic techniques in patients with Parkinson's disease plays an important role in minimizing complications and patient morbidity and mortality. Anesthetic concerns in patients with Parkinson's disease are the presence or absence of interactions with anti-Parkinson's drugs that the patient is taking, decreased organ function due to old age, such as decreased cardiovascular, respiratory, and autonomic nerve function. In this case, the patient with Parkinson's disease will undergo repositioning of the left femoral head due to the dislocation. We chose regional anesthesia because it has several advantages over general anesthesia. The results during and after surgery were good, there were no complications and the patient returned to the room.